First person - Sneh Harsh (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Sneh Harsh is first author on 'Zika virus non-structural protein NS4A restricts eye growth in Drosophila through regulation of JAK/STAT signaling', published in DMM. Sneh conducted the research described in this article while a postdoctoral researcher in Ioannis Eleftherianos's lab at The George Washington University, Washington, DC, USA. She is now a postdoctoral researcher in the lab of Erika Bach at NYU Langone Health, New York, NY, USA, investigating host pathophysiology upon Zika virus infection using Drosophila developing organs as the model system.